Developing Sustainable Technological Pedagogical Content Knowledge (S-TPACK) in Teaching Science - Zahra Sadat Roozafzai (Universal Education Jurnal Teaching and Learning, 2025)
This mixed-methods study introduces the concept of Sustainable Technological Pedagogical Content Knowledge (Sustainable TPACK), extending the TPACK framework with a focus on eco-friendly technology integration in science education. The research aimed to operationalize the Sustainable TPACK framework and explore its application in science teaching contexts. A survey was administered to assess in-service science teachers' self-reported Sustainable TPACK levels, followed by in-depth case studies involving classroom observations, interviews, and document analysis. The findings demonstrated that science teachers generally possessed moderate to high levels of Sustainable TPACK and faced challenges in implementing eco-friendly technology, which could be overcome through collaboration and professional development opportunities. The study highlights the need for targeted initiatives supporting science educators in developing Sustainable TPACK, fostering environmental stewardship among students, and addressing domain-specific challenges. Future research may examine the impact of Sustainable TPACK on student learning outcomes and the effectiveness of various professional development strategies in promoting this framework among science educators.